Dinamika Kepatuhan Wajib Pajak di Indonesia: Antara Kesadaran Individu dan Efektivitas Sistem Perpajakan - Ni Komang Mira Canthika Kencana Wati Karang; Ni Kadek Dwi Anggi Maharani; Sindy Anggriana; Luh Oktavia Sulistiawati; Chosy Agatha Br Colia (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
Taxpayer compliance is a crucial factor in optimizing state revenue to support national development financing independently. This study aims to analyze the dynamics of taxpayer compliance in Indonesia by examining two main aspects: individual awareness and the effectiveness of the tax system. The method used is a descriptive qualitative approach with a literature review of various national journals from the last five years. The findings indicate that taxpayer compliance is influenced not only by internal factors such as knowledge, awareness, and tax morale but also by external factors such as tax service quality, system digitalization, and regulatory complexity. Tax reforms and the implementation of digital systems such as e-filing and e-billing have been proven to significantly increase taxpayer compliance through ease of access and reporting efficiency. However, real challenges remain, such as low community tax literacy and perceptions of unfairness regarding the management of tax funds by the government. Therefore, a strong synergy is needed between increasing public awareness through continuous education and improving the taxation system to create sustainable and optimal compliance. Improving transparency and accountability in the management of tax funds is a strategic step to strengthen public trust in tax authorities in Indonesia.